The Supraorbital Keyhole Craniotomy Approach for Olfactory Implantation: A Radiological Feasibility Study - Sterlin, Lauren J.; Saeedi, Arman; Broaddus, William C.; Coelho, Daniel H. (Journal of Neurological Surgery Part B: Skull Base, 2025)
Olfactory implants to address anosmia have gained interest in recent years. Existing transnasal and transcranial approaches to the olfactory bulb (OB) have potential complications. We aim to determine whether transcranial supraorbital keyhole craniotomy (SOKC) provides adequate and safe access to the OB. Secondary outcomes include highlighting specific anatomical obstructions and impacts of patient characteristics.This is a retrospective cohort study.This study was conducted at the Tertiary Academic Medical Center.Fifty fine-cut computed tomographies of the sinuses in consecutive adult patients (50% male) were analyzed. Image processing was performed using syngo.via to assess whether there was a clear path from points on the exterior skull to the anterior or posterior OB. Using five points based on the SOKC technique on the exterior skull, lines were drawn from each point to the ipsilateral anterior and posterior OB resulting in 1,000 pathways. Pathways were reconstructed and analyzed for violations of the orbit, orbital bone, or sinuses.A total of 96% of the subjects had at least one unobstructed pathway to the OB. The route most commonly unobstructed (90%) was 2P (2 cm above the supraorbital notch to posterior bulb). The posterior OB was less obstructed than the anterior (56, 112; p = 0.00002). The most common obstruction was an ipsilateral sinus.The SOKC may be an effective and safe approach for an olfactory implant in many patients. The posterior OB had a clearer approach with less obstruction. By avoiding injury to the nasal mucosa, orbit, sinuses, or traversing the skull base, this approach may prove advantageous over transnasal approaches for olfactory implantation in select patients.
Keywords: anosmia treatment; olfactory implantation; olfactory bulb access